Transformation Of Integrative Curriculum Management Islamic Boarding School Located In State Madrasah In Malang City - Zamanina, Kunti Zahra; Ali, Nur; Zahro, Fatimatuz; Bintang M., Nayya Hajar (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v10i1.3772, 2025)
Many public madrasas in Malang have undergone institutional transformation, including the establishment of integrated Islamic boarding schools within the madrasa and the adoption of an integrative curriculum to strengthen the realization of their educational vision and mission. This study aims to analyze the administration of the integrated curriculum implemented at Ma’had Al-Madany MTsN 1 Kota Malang and examine its effects on student development. The research employed a qualitative case study design involving 239 participants, consisting of the head of the Ma’had, teachers, murabbi–murabbiyah, and selected students. Data were collected through in-depth interviews, participant observation of daily Ma’had activities, and documentation of institutional records. The data were analyzed using thematic analysis through stages of data reduction, data display, and conclusion drawing. The findings reveal that the integrative curriculum supported by alignment between institutional vision, collaborative planning, and coherent program implementation enhances students’ academic achievement, strengthens religious attitudes and character, improves social competencies, and reinforces institutional credibility. The novelty of this study lies in demonstrating how an embedded pesantren model within a state madrasa can serve as a driver of academic–spiritual integration through systematic collaboration between the two institutions. These findings offer a transferable model for state madrasas in other regions and provide practical implications for Islamic educational institutions seeking effective pathways for institutional innovation and curriculum integration